“I Guess this is Growing Up” Analysis of Pop-Punk’s Regained Popularity and Its Shift From Bands to Personas. - Ruth, Nicolas; Jacke, Christoph (Persona Studies)
This research article examines the transformation of pop-punk from bands to solo artists and how the genre regained popularity due to new popular personalities and the transmedia engagement in social media and with established media. Through a three-pronged approach, this studyadopts phenomenological, theoretical, and empirical perspectives to understand the transition and regained popularity fully. The phenomenological angle delves into the case studies of musicians, revealing key factors behind the shift to solo artists in pop-punk. Theoretical explanations contextualize the phenomenon within broader cultural frameworks, considering industry and transmedia dynamics, audience preferences, and technological advancements. Empirical evidence, including statistical data from socialmedia profiles, quantifies the impact of the shift.This study contributes to a comprehensive understanding of pop-punk's transformation, offering an exploration of its past, present, and future within the ever-evolving music industries and transmedia landscapes
Keywords: Pop-punk; Popular Musical Personas; Solo Artists; SocialMedia; Transmedia; TikTok

Stars, Anti-Stars, Anti-Star-Stars Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions - Jacke, Christoph (Persona Studies)

Stars, Anti-Stars, Anti-Star-Stars. Transmedia Texts and Contexts of Popular Music and Media. Some Theoretical Assumptions. - Jacke, Christoph (Persona Studies)
The phenomenon of stars and celebrities in media cultures – and especially in popular music cultures – seems to be omnipresent. At the same time, there is an astounding lack of analysis and research on these media personalities and personas, and international celebrity studies only recently a developing new field. Similarly, these kinds of observations are still very rare especially in German sociology as well as communication, media, culture and popular music studies. In this article, I therefore want to concentrate on the foundations of studying stars and celebrities within the attention economies by undertaking a theoretical transmedia-cultural framing of media personas and suggesting a typology. This ensuing typology of stars, anti-stars, and anti-star stars – especially within popular music cultures – demonstrates how stars and celebrities and their quantities and qualities of success and peer-group specific values coming form programs of (media and music) culture can serve as persona-seismographs of socio-cultural change between tradition and innovation
Keywords: Stars; Celebrities; Popular Music; Transmedia Culture; Personas

Self-Assembled Block Copolymer Thin Films and Their Applications (Polymers)

Does Explainability Require Transparency? - Esposito, Elena (Sociologica)
Dealing with opaque algorithms, the frequent overlap between transparency and explainability produces seemingly unsolvable dilemmas, as the much-discussed trade-off between model performance and model transparency. Referring to Niklas Luhmann's notion of communication, the paper argues that explainability does not necessarily require transparency and proposes an alternative approach. Explanations as communicative processes do not imply any disclosure of thoughts or neural processes, but only reformulations that provide the partners with additional elements and enable them to understand (from their perspective) what has been done and why. Recent computational approaches aiming at post-hoc explainability reproduce what happens in communication, producing explanations of the working of algorithms that can be different from the processes of the algorithms.
Keywords: Explainable AI; Transparency; Explanation; Communication; Sociological systems theory

Explaining Machines: Social Management of Incomprehensible Algorithms. Introduction - Esposito, Elena (Sociologica)
This short introduction presents the symposium ‘Explaining Machines’. It locates the debate about Explainable AI in the history of the reflection about AI and outlines the issues discussed in the contributions.
Keywords: Explainable AI; Inexplicability; Transparency; Explanation; Opacity; Contestability

End-to-End Dereverberation, Beamforming, and Speech Recognition in A Cocktail Party - Zhang, Wangyou; Chang, Xuankai; Boeddeker, Christoph; Nakatani, Tomohiro; Watanabe, Shinji; Qian, Yanmin (IEEE/ACM Transactions on Audio, Speech, and Language Processing)
Far-field multi-speaker automatic speech recognition (ASR) has drawn increasing attention in recent years. Most existing methods feature a signal processing frontend and an ASR backend. In realistic scenarios, these modules are usually trained separately or progressively, which suffers from either inter-module mismatch or a complicated training process. In this paper, we propose an end-to-end multi-channel model that jointly optimizes the speech enhancement (including speech dereverberation, denoising, and separation) frontend and the ASR backend as a single system. To the best of our knowledge, this is the first work that proposes to optimize dereverberation, beamforming, and multi-speaker ASR in a fully end-to-end manner. The frontend module consists of a weighted prediction error (WPE) based submodule for dereverberation and a neural beamformer for denoising and speech separation. For the backend, we adopt a widely used end-to-end (E2E) ASR architecture. It is worth noting that the entire model is differentiable and can be optimized in a fully end-to-end manner using only the ASR criterion, without the need of parallel signal-level labels. We evaluate the proposed model on several multi-speaker benchmark datasets, and experimental results show that the fully E2E ASR model can achieve competitive performance on both noisy and reverberant conditions, with over 30% relative word error rate (WER) reduction over the single-channel baseline systems.

Steady states of Λ-type three-level systems excited by quantum light with various photon statistics in lossy cavities - Rose, Hendrik; Tikhonova, O V; Meier, Torsten; Sharapova, Polina (New Journal of Physics)
Abstract The interaction between quantum light and matter is being intensively studied for systems that are enclosed in high- Q cavities which strongly enhance the light–matter coupling. Cavities with low Q -factors are generally given less attention due to their high losses that quickly destroy quantum systems. However, bad cavities can be utilized for several applications, where lower Q -factors are required, e.g., to increase the spectral width of the cavity mode. In this work, we demonstrate that low- Q cavities can be beneficial for preparing specific electronic steady states when certain quantum states of light are applied. We investigate the interaction between quantum light with various statistics and matter represented by a Λ-type three-level system in lossy cavities, assuming that cavity losses are the dominant loss mechanism. We show that cavity losses lead to non-trivial electronic steady states that can be controlled by the loss rate and the initial statistics of the quantum fields. We discuss the mechanism of the formation of such steady states on the basis of the equations of motion and present both analytical expressions and numerical simulations for such steady states.
Keywords: General Physics and Astronomy

Auswirkung der Theologie auf das rechtsphilosophische Denken der Muʿtazila: Lektüre bei al-Qāḍī ʿAbd al-Ǧabbār - Abdelrahem, Mohammed (Zeitschrift für Recht und Islam / Journal of Law & Islam)
Im Wesentlichen wird im Beitrag die Frage beantwortet, inwieweit die muʿtazilitisch-rationale Theologie die Rechtsphilosophie ʿAbd al-Ǧabbārs beeinflusst. Vor allem werden als Beispiele die Auseinandersetzung ʿAbd al-Ǧabbārs mit den verschiedenen Rechtsquellen und deren Aspekte systematisch-rechtlich dargestellt und die Frage nach der Zentralität des Menschen, dessen Vernunft und Wohl fokussiert. Dafür bedient sich der Beitrag der uṣūlitischen Werke und Beiträge ʿAbd al-Ǧabbārs, in denen dieser eine besondere, von seinem kalām-Ansatz stark geprägte Methodologie verfolgt. Mit seinen uṣūl-Werken konstruierte der šāfiʿitische Muʿtazilit ʿAbd al-Ǧabbār, Systematiker der muʿtazilitischen Dogmenlehre, eine rechtsphilosophische, rational geprägte Theorie und gilt damit als eine der bedeutendsten ›Stationen‹ auf dem Weg der Methodologie der Theolog:innen sowie des Verhältnisses zwischen der kalām-Lehre und den uṣūl al-fiqh. Bei seiner Beschäftigung mit den verschiedenen Rechtsquellen des islamischen Rechts führt er drei Voraussetzungen für ihre gesetzgebende Funktion an. Dabei handelt es sich um Aspekte, die die Rechtsbelege zu berücksichtigen haben und somit eine Art ethische Perspektive bilden: den Menschen als Empfänger des normativen Texts, die Vernunft als Instrument der Rechtswahrnehmung und das Wohl der Menschen als Ziel der Rechtsbelege.

Continuous variable multimode quantum states via symmetric group velocity matching - Roman-Rodriguez, V; Brecht, Benjamin; Srinivasan, K; Silberhorn, Christine; Treps, N; Diamanti, E; Parigi, V (New Journal of Physics)

Improved non-linear devices for quantum applications - Gil López, Jano; Santandrea, Matteo; Roland, Ganaël; Brecht, Benjamin; Eigner, Christof; Ricken, Raimund; Quiring, Viktor; Silberhorn, Christine (New Journal of Physics)

Approximate nonlinear wave solutions of the coupled two-component Gross–Pitaevskii equations with spin–orbit interaction - Belobo, Didier Belobo; Meier, Torsten (New Journal of Physics)

The new V-Model of 2206 and its validation - Gräßler, Iris; Hentze, Julian (at-Automatisierungstechnik 68(5))

Review Hagengruber Le Ru Émilie Du Châtelet Philosophe - Hagengruber, Ruth (H-France Net)

Informationskompetenz durch E-Learning? Durch Lernvideos nach Literatur suchen - Hahn, Charlotte Anna (die hochschullehre)
The aim of this study was to find out whether teaching how to search for literature would be more beneficial to students and teachers if done online through short videos rather than in person during course time. To find out whether online videos are more beneficial, two courses were asked to fill in questionnaires, one at the beginning and one at the end of the semester. One of the courses received the input online via videos and were given an exercise to put the newly learned skills to use, the other course served as a control group and learned how to search for literature during the course. The results show that while the difference between the two groups is not significant, the videos can still be regarded as being more beneficial than teaching the necessary skills during course time.
Keywords: E-Learning; information competence; literature; library; research

Rezension zu: Bernardo Bátiz-Lazo: Cash and Dash. How ATMs and Computers Changed Banking - Schmitt, Martin (Vierteljahrschrift für Sozial- und Wirtschaftsgeschichte)
Keywords: Wirtschaftsgeschichte; Bankengeschichte; Geldautomat; ATM; Geschichte; Technikgeschichte

Improving SPDC single-photon sources via extended heralding and feed-forward control - Massaro, Marcello; Meyer-Scott, Evan; Montaut, Nicola; Herrmann, Harald; Silberhorn, Christine (New Journal of Physics)

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)
Keywords: pc2-ressources

Characterisation of fabrication inhomogeneities in Ti:LiNbO3 waveguides - Santandrea, Matteo; Stefszky, Michael; Roeland, Ganaël; Silberhorn, Christine (New Journal of Physics)

Fabrication limits of waveguides in nonlinear crystals and their impact on quantum optics applications - Santandrea, Matteo; Stefszky, Michael; Ansari, Vahid; Silberhorn, Christine (New Journal of Physics)

Eigenvalue measurement of topologically protected edge states in split-step quantum walks - Nitsche, Thomas; Geib, Tobias; Stahl, Christoph; Lorz, Lennart; Cedzich, Christopher; Barkhofen, Sonja; Werner, Reinhard F; Silberhorn, Christine (New Journal of Physics)

Narratives of Vicarious Experience in Oral History Interviews with Craft Artists - Mildorf, Jarmila (Journal of Pragmatics)

Controllable high-speed polariton waves in a PT-symmetric lattice - Ma, Xuekai; Kartashov, Yaroslav Y; Gao, Tingge; Schumacher, Stefan (New Journal of Physics)

High-speed velocimetry in microfluidic protein mixers using confocal fluorescence decay microscopy - Inguva, Venkatesh; Rothstein, Jonathan P.; Bilsel, Osman; Perot, Blair J. (Experiments in Fluids)

Quantum state and mode profile tomography by the overlap - Tiedau, J; Shchesnovich, V S; Mogilevtsev, D; Ansari, V; Harder, G; Bartley, Tim; Korolkova, N; Silberhorn, Christine (New Journal of Physics)

Systematic study of the influence of coherent phonon wave packets on the lasing properties of a quantum dot ensemble - Wigger, Daniel; Czerniuk, Thomas; Reiter, Doris E; Bayer, Manfred; Kuhn, Tilmann (New Journal of Physics)
Coherent phonons can greatly vary light–matter interaction in semiconductor nanostructures placed inside an optical resonator on a picosecond time scale. For an ensemble of quantum dots (QDs) as active laser medium, phonons are able to induce a large enhancement or attenuation of the emission intensity, as has been recently demonstrated. The physics of this coupled phonon–exciton–light system consists of various effects, which in the experiment typically cannot be clearly separated, in particular, due to the complicated sample structure a rather complex strain pulse impinges on the QD ensemble. Here we present a comprehensive theoretical study how the laser emission is affected by phonon pulses of various shapes as well as by ensembles with different spectral distributions of the QDs. This gives insight into the fundamental interaction dynamics of the coupled phonon–exciton–light system, while it allows us to clearly discriminate between two prominent effects: the adiabatic shifting of the ensemble and the shaking effect. This paves the way to a tailored laser emission controlled by phonons.

Extracting the physical sector of quantum states - Mogilevtsev, D; Teo, Y S; Řeháček, J; Hradil, Z; Tiedau, J; Kruse, R; Harder, G; Silberhorn, Christine; Sanchez-Soto, L L (New Journal of Physics)
Keywords: General Physics and Astronomy

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Toolbox for the design of LiNbO3-based passive and active integrated quantum circuits - Sharapova, Polina; Luo, Kai Hong; Herrmann, Harald; Reichelt, Matthias; Meier, Torsten; Silberhorn, Christine (New Journal of Physics)

Driven discrete time quantum walks - Hamilton, Craig S; Barkhofen, Sonja; Sansoni, Linda; Jex, Igor; Silberhorn, Christine (New Journal of Physics)

Quantum walks with dynamical control: graph engineering, initial state preparation and state transfer - Nitsche, Thomas; Elster, Fabian; Novotný, Jaroslav; Gábris, Aurél; Jex, Igor; Barkhofen, Sonja; Silberhorn, Christine (New Journal of Physics)

Zwischen Wissenschaft und Lebenswelt. Entwicklung, Stand und Zukunftsperspektiven haushaltsbezogener Bildung. - Schlegel-Matthies, Kirsten

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai-Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

A population-competition model for analyzing transverse optical patterns including optical control and structural anisotropy - Tse, Y C; Chan, Chris K P; Luk, M H; Kwong, N H; Leung, P T; Binder, R; Schumacher, Stefan (New Journal of Physics)

Directly comparing entanglement-enhancing non-Gaussian operations - Bartley, Tim; Walmsley, Ian A (New Journal of Physics)

Direct generation of genuine single-longitudinal-mode narrowband photon pairs - Luo, Kai Hong; Herrmann, Harald; Krapick, Stephan; Brecht, Benjamin; Ricken, Raimund; Quiring, Viktor; Suche, Hubertus; Sohler, Wolfgang; Silberhorn, Christine (New Journal of Physics)

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Multipoles and vortex multiplets in multidimensional media with inhomogeneous defocusing nonlinearity - Driben, Rodislav; Dror, Nir; Malomed, Boris A.; Meier, Torsten (New Journal of Physics)
We predict a variety of composite quiescent and spinning two- and three-dimensional (2D and 3D) self-trapped modes in media with a repulsive nonlinearity whose local strength grows from center to periphery. These are 2D dipoles and quadrupoles, and 3D octupoles, as well as vortex–antivortex pairs and quadruplets. Unlike other multidimensional models, where such complex bound states either do not exist or are subject to strong instabilities, these modes are remarkably robust in the present setting. The results are obtained by means of numerical methods and analytically, using the Thomas–Fermi approximation. The predicted states may be realized in optical and matter-wave media with controllable cubic nonlinearities

Formation and interaction of resonance chains in the open three-disk system - Weich, T; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)

Formation and interaction of resonance chains in the open three-disk system - Weich, Tobias; Barkhofen, Sonja; Kuhl, U; Poli, C; Schomerus, H (New Journal of Physics)
Keywords: General Physics and Astronomy

A source of polarization-entangled photon pairs interfacing quantum memories with telecom photons - Clausen, C; Bussières, F; Tiranov, A; Herrmann, Harald; Silberhorn, Christine; Sohler, W; Afzelius, M; Gisin, N (New Journal of Physics)
Keywords: General Physics and Astronomy

Three-dimensional hybrid vortex solitons - Driben, Rodislav; Kartashov, Yaroslav V.; Malomed, Boris A.; Meier, Torsten; Torner, Lluis (New Journal of Physics)
We show, by means of numerical and analytical methods, that media with a repulsive nonlinearity which grows from the center to the periphery support a remarkable variety of previously unknown complex stationary and dynamical three-dimensional (3D) solitary-wave states. Peanut-shaped modulation profiles give rise to vertically symmetric and antisymmetric vortex states, and novel stationary hybrid states, built of top and bottom vortices with opposite topological charges, as well as robust dynamical hybrids, which feature stable precession of a vortex on top of a zero-vorticity soliton. The analysis reveals stability regions for symmetric, antisymmetric, and hybrid states. In addition, bead-shaped modulation profiles give rise to the first example of exact analytical solutions for stable 3D vortex solitons. The predicted states may be realized in media with a controllable cubic nonlinearity, such as Bose–Einstein condensates.

Theory of quantum frequency conversion and type-II parametric down-conversion in the high-gain regime - Christ, Andreas; Brecht, Benjamin; Mauerer, Wolfgang; Silberhorn, Christine (New Journal of Physics)

An efficient integrated two-color source for heralded single photons - Krapick, S; Herrmann, Harald; Quiring, V; Brecht, Benjamin; Suche, H; Silberhorn, Christine (New Journal of Physics)

Aharonov–Bohm rings with strong spin–orbit interaction: the role of sample-specific properties - Nichele, F; Komijani, Y; Hennel, S; Gerl, C; Wegscheider, W; Reuter, Dirk; Wieck, A D; Ihn, T; Ensslin, K (New Journal of Physics)

Spatio-spectral characteristics of parametric down-conversion in waveguide arrays - Kruse, R; Katzschmann, F; Christ, A; Schreiber, A; Wilhelm, S; Laiho, K; Gábris, A; Hamilton, C S; Jex, I; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Entanglement quasiprobabilities of squeezed light - Sperling, Jan; Vogel, W (New Journal of Physics)

Exponentially enhanced quantum communication rate by multiplexing continuous-variable teleportation - Christ, Andreas; Lupo, Cosmo; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Characteristics of displaced single photons attained via higher order factorial moments - Laiho, Kaisa; Avenhaus, Malte; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

From quantum pulse gate to quantum pulse shaper—engineered frequency conversion in nonlinear optical waveguides - Brecht, Benjamin; Eckstein, Andreas; Christ, Andreas; Suche, Hubertus; Silberhorn, Christine (New Journal of Physics)

Probing multimode squeezing with correlation functions - Christ, Andreas; Laiho, Kaisa; Eckstein, Andreas; Cassemiro, Katiúscia N; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Multi-walker discrete time quantum walks on arbitrary graphs, their properties and their photonic implementation - Rohde, Peter P; Schreiber, Andreas; Štefaňák, Martin; Jex, Igor; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Como podemos definir vigilância? - Fuchs, Christian (MATRIZes)

Observation of orientation- andk-dependent Zeeman spin-splitting in hole quantum wires on (100)-oriented AlGaAs/GaAs heterostructures - Chen, J C H; Klochan, O; Micolich, A P; Hamilton, A R; Martin, T P; Ho, L H; Zülicke, U; Reuter, Dirk; Wieck, A D (New Journal of Physics)

Optical probing of spin dynamics of two-dimensional and bulk electrons in a GaAs/AlGaAs heterojunction system - Rizo, P J; Pugzlys, A; Slachter, A; Denega, S Z; Reuter, Dirk; Wieck, A D; van Loosdrecht, P H M; van der Wal, C H (New Journal of Physics)

Accessing the purity of a single photon by the width of the Hong–Ou–Mandel interference - Cassemiro, Katiúscia N; Laiho, Kaisa; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Optimized generation of heralded Fock states using parametric down-conversion - Brańczyk, Agata M; Ralph, T C; Helwig, Wolfram; Silberhorn, Christine (New Journal of Physics)
Keywords: General Physics and Astronomy

Feasibility of free space quantum key distribution with coherent polarization states - Elser, D.; Bartley, Tim; Heim, B.; Wittmann, Ch; Sych, D.; Leuchs, G. (New Journal of Physics)
We demonstrate for the first time the feasibility of free space quantum key distribution with continuous variables under real atmospheric conditions. More specifically, we transmit coherent polarization states over a 100 m free space channel on the roof of our institute's building. In our scheme, signal and local oscillator (LO) are combined in a single spatial mode, which auto-compensates atmospheric fluctuations and results in an excellent interference. Furthermore, the LO acts as a spatial and spectral filter, thus allowing unrestrained daylight operation.

Quantum dot as thermal rectifier - Scheibner, R; König, M; Reuter, Dirk; Wieck, A D; Gould, C; Buhmann, H; Molenkamp, L W (New Journal of Physics)

Ab initio study of the half-metal to metal transition in strained magnetite - Friák, Martin; Schindlmayr, Arno; Scheffler, Matthias (New Journal of Physics)
Using density-functional theory, we investigate the stability of the half-metallic ground state of magnetite under different strain conditions. The effects of volume relaxation and internal degrees of freedom are fully taken into account. For hydrostatic compression, planar strain in the (001) plane and uniaxial strain along the [001] direction, we derive quantitative limits beyond which magnetite becomes metallic. As a major new result, we identify the bond length between the octahedrally coordinated iron atoms and their neighbouring oxygen atoms as the main characteristic parameter, and we show that the transition occurs if external strain reduces this interatomic distance from 2.06 Å in equilibrium to below a critical value of 1.99 Å. Based on this criterion, we also argue that planar strain due to epitaxial growth does not lead to a metallic state for magnetite films grown on (111)-oriented substrates.

Lagrangian structures and transport in turbulent magnetized plasmas - Padberg, Kathrin; Hauff, Thilo; Jenko, Frank; Junge, Oliver (New Journal of Physics)

Magnetization of bilayer two-dimensional electron systems - Bominaar-Silkens, I M A; Schaapman, M R; Zeitler, U; Christianen, P C M; Maan, J C; Reuter, Dirk; Wieck, A D; Schuh, D; Bichler, M (New Journal of Physics)

Mischbauweise sorgt für frischen Wind - Meschut, Gerson (Konstruktion)

Lipirea în combinatie cu îmbinarile obtinute prin deformare - Hahn, O.; Koyro, M.; Meschut, Gerson (sudura)

Hybridfügen – Grundlagen, Technologie, Anwendungen - Meschut, Gerson (DVM-Bericht 668)

Medienbildung und Gesellschaft

Eine quasistationäre Meßmethode zur Ermittlung der Wärmeleitfähigkeit polymerer Zwischenschichten in Abhängigkeit von der Temperatur - Koyro, M.; Meschut, Gerson (Tagungsband zur Veranstaltung Werkstoffprüfung 1999)